Liquid Cooling of Laser-driven Head Light Employing Heat Spreader Manufactured by 3D Metal Printing - Lee, Yonghan; Park, Sangki; Byun, Changho; Lee, Sun-Kyu (International Journal of Precision Engineering and Manufacturing-Green Technology, 5(2), 2018)
Laser-driven white lighting is attracting attention due to its advantages compared to LED-based white lighting systems, such as high luminous intensity, high efficacy, and the possibility of miniaturization. The optical efficiency of a lighting system based on high-power laser diodes (LDs) is highly affected by the temperature of the LD and phosphor, meaning cooling is critical for many practical applications. The junction temperature must be properly predicted and controlled to prevent failure of the LD. This paper presents a thermal dynamic model of an LD cooling system for predicting the junction temperature and an experiment to validate the model. The system consists of an LD, heat spreader, heat sink, and liquid pump. The system was placed inside a test chamber, and the temperature of each element was measured under various ambient temperatures. The results were then compared with the simulation results. A heat spreader was designed with liquid cooling channels based on the model in consideration of both the thermal resistance and pressure drop. The spreader was then fabricated using 3D metal printing. The spreader provided higher performance compared with thermoelectric cooling.